From Subjects to Partners: Rethinking Research Methodologies through Citizen Science - De Marchi, Bruna (La Medicina del Lavoro, 2025)
The article will first introduce a general definition of Citizen Science (section 1), followed by an excursion of its foundations and of the different understandings and ways of applying it, with examples drawn from diverse research and policy areas (section 2). It will then focus more closely on the field of health and the environment (section 3), including occupational medicine (subsection 3.1), community response to environmental risks (section 3.2), biomonitoring (sub-section 3.3), and human biomonitoring (subsection 3.4). Section 4 will address some of the advantages (section 4.1) and challenges (section 4.2) of adopting CS in research and policy. Finally, section 5 will trace the legislative and normative background of participatory approaches and points to the challenges ahead.